Penerapan Aspek Spiritualitas dengan Pemenuhan Kebutuhan Spiritual Pada Pasien - Achmad Amiruddin; Murniati Murniati (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Background; nurses believe that humans are bio-psycho-socio-cultural and spiritual beings who are intact and respond to changes that occur, among others, due to health problems and irregularities in fulfilling needs. Aim; know the relationship between the application of spiritual aspects of nurses with the fulfillment of spiritual needs in inpatients at Barombong Health Center. Method; Descriptive analytic research design using the Cross-sectional design method to take measurements or observations at the same time with purposive sampling technique sampling. Data obtained through a questionnaire that was processed using the SPSS computer program. Univariate and bivariate data analysis and description. Result; The statistical test obtained the value of ρ = 0.034 <α = 0.05, there is a relationship between the application of the spirituality aspects of nurses and the fulfillment of the spiritual needs of patients. Conclusion; There is a relationship between the application of the spirituality aspects of nurses with the fulfillment of spiritual needs for inpatients. There needs to be a strategy in improving health services, especially in applying the spiritual needs of the patient.